An Empirical Analysis of the Impact of Unemployment on Economic Growth in Zimbabwe - Zivanomoyo, James; Mukoka, Shame (Archives of Business Research, 2015)
This study examined the impact of unemployment on economic growth in Zimbabwe for the period 1982 to 2013. In this study we use the ordinary least squares (OLS) to estimate the regression equation. The first step is to make the data stationary to avoid spurious regression. Based on the stationarity test results, cointegration tests were conducted to test for the existence of a long run relationship between economic growth and its determinants. The Error Correction Model (ECM) was also employed to establish the short run dynamics and speed of adjustment to the long run. The estimation results for both the long run and short run models revealed that unemployment has a significant influence on productivity growth. Also shown from the results is the negative relationship between unemployment and economic growth.